“KEY ENABLERS FOR POSTPONEMENT: FROM A LITERATURE REVIEW TO AN INTEGRATED CONCEPTUAL FRAMEWORK” - Andreou, Andreas (2012)
Throughout the supply chain literature, there has been considerable interest from both managers and practitioners for the application of postponement. Although postponement has a long history in both academia and business, very few studies have been concentrated on identifying the enablers that facilitate such a supply chain strategy. Bridging this gap in the literature, the current study focuses on identifying the enablers of postponement application and, also, to present a framework for guiding successful implemenetation. Consequently, after identifying 48 rigorous studies for acquiring reliable data, 6 key enablers for successful implementation have been recognised. These are product capability, process cabapility, agile supply chain, business climate, organizational adaptability and, finally, integrated information systems. Furthermore, the identified conceptual framework can be used by researchers, in order to test it in real business environments and, thus, to evaluate its external validity. On the other hand, practitioners may also consider the findings of this research very fruitful for adopting postponement strategy and also can use the emergent framework as a ‘roadmap’, in order to apply postponement successfully.